Lethal effect of piperaceous extracts on palm red mite, Raoiella indica (Acari: Tenuipalpidae) - Pinheiro, Esmael Cunha; Vasconcelos, Geraldo José Nascimento de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
Since the introduction of the red palm mite, Raoiella indica, in Brazil, some control methods have been studied to suppress this pest, such as the quarantine, chemical, biological and plant extract control. This study aimed to evaluate the lethal potential of aqueous extracts of Piper aduncum, P. callosum, P. hostmannianum, P. marginatum and P. peltatum against R. indica. The residual contact action of the extracts applied by immersion at concentrations of 0, 5, 10, 15, 20, 25 and 30% was evaluated, and the action evaluated at three exposure periods, 24, 48 and 72 h. From the mortality data at the different concentrations and at each exposure period, corrected mortalities and lethal concentrations (LC25% and LC50%) of the piperaceous extracts for the R. indica population were determined. Only the extracts of P. aduncum, at 5% after 24 h of exposure, and P. callosum, in this same concentration at all times of exposure, did not present corrected mortality different from the control. The LC25% ranged from 0.99 to 13.02%, 1.29 to 7.89% and 1.82 to 7.69%, respectively, for the 24, 48 and 72 h exposure periods. Already the LC50%, respectively for the same exposure periods, ranged from 2.27 to 21.29%, 2.33 to 13.26% and 2.84 to 10.94%. The aqueous leaf extracts of the five species of piperaceous showed toxicological effect the R. indica population.